Impact of digital transformation on knowledge-sharing activities of accounting students at universities in VietNam - Phan Hương, Thảo; Giang Pham, Tra; Mi Pham, Tra; Anh Ta, Lan (International Journal of Scientific Research and Management (IJSRM), 2023)
The fourth industrial revolution is a journey with the breakthrough of digital technologies leading to the intelligence of all aspects of society. Digital transformation is the way to go in the development of the 4.0 industrial revolution and an invaluable opportunity to develop the country. In today's social era, we are almost no stranger to the phrase “digital transformation”. With the success of the fourth industrial revolution, digital transformation is now an inevitable trend, a matter of survival for countries, organizations, businesses, and consumers around the world. This is how to apply digital technology logically and effectively in all aspects of life, from management, production, business, etc. Or the process of digital transformation is to move our activities from the real world to the virtual world in cyberspace. In the world, many countries have been implementing digital transformation strategies such as in the UK, Australia, Denmark, Estonia... The content of digital transformation is very wide and diverse, but it has some main content in common, including digital government (such as online public services, open data), digital economy (such as digital finance, e-commerce), digital society (such as education, health care, culture), and digital transformation in key industries (such as agriculture, tourism, electricity, transportation).